2022
DOI: 10.1029/2022pa004423
|View full text |Cite
|
Sign up to set email alerts
|

A10Be Moraine Chronology of the Last Glaciation and Termination at 49°N in the Mongolian Altai of Central Asia

Abstract: Determining what caused the global Last Glaciation and last glacial termination, despite opposing orbital summer insolation signatures between the polar hemispheres, remains a puzzle of paleoclimatology. This problem can be addressed by comparing chronologies of glaciation from different latitudes and different climatic regimes in both hemispheres. Here, we present a 10Be surface‐exposure chronology of glacial landforms constructed during and since the local Last Glaciation in the continental environment of Ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 117 publications
0
7
0
Order By: Relevance
“…in the Altai Mountains during MIS 2 (29–14 ka; Martinson et al, 1987), related to temperature change in Tibet (Guliya Ice Cap). (a) this study (grey dots: outliers); (b) Reuther et al, 2006; Agatova et al, 2020; Herget et al, 2020; (c) Gribenski et al, 2016; (d) Gribenski et al, 2018; (e) Radue, 2018; (f) Strand et al, 2022 [arithmetic mean (three to nine samples) for five moraines and three erratic sets]; (g) Blomdin et al, 2018; (h) Ganyuskin et al, 2018a; (i) Dong et al, 2020 (outside the location map); (j) Thompson et al, 2005. Ages of the moraines and erratic boulders are mostly from SED, while GLOF ages resulted from different dating methods: SED on flood‐associated boulders, OSL dating on flood and lacustrine deposits and radiocarbon dating on subaerial deposits.…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…in the Altai Mountains during MIS 2 (29–14 ka; Martinson et al, 1987), related to temperature change in Tibet (Guliya Ice Cap). (a) this study (grey dots: outliers); (b) Reuther et al, 2006; Agatova et al, 2020; Herget et al, 2020; (c) Gribenski et al, 2016; (d) Gribenski et al, 2018; (e) Radue, 2018; (f) Strand et al, 2022 [arithmetic mean (three to nine samples) for five moraines and three erratic sets]; (g) Blomdin et al, 2018; (h) Ganyuskin et al, 2018a; (i) Dong et al, 2020 (outside the location map); (j) Thompson et al, 2005. Ages of the moraines and erratic boulders are mostly from SED, while GLOF ages resulted from different dating methods: SED on flood‐associated boulders, OSL dating on flood and lacustrine deposits and radiocarbon dating on subaerial deposits.…”
Section: Discussionmentioning
confidence: 82%
“…While a re‐evaluation of glacial chronologies in the Central Asia concluded that there was no significant ice expansion during MIS 3 (59–29 ka; Gribenski et al, 2018, and references therein), as already suggest by Lehmkuhl et al (2016) for the Mongolian Altai, few studies document a major glacier advance during MIS 3 in the Altai Mountains: a Turgen‐Asgat moraine in drier Ikh Turgen Mountains is dated to c . 45 ka (Blomdin et al, 2018), the outermost one of the Khoton Nuur complex is dated to 35.4 ka (Strand et al, 2022), while Dong et al (2020) propose a local LGM at 34.1 ka in the Xiaokelanhe River basin.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations